SOCIAL REASSURANCE WOMENS PROGRAMMES OF DMK GOVERNMENT (1989-1991) - G. Karihalan; N. Ashadevi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Since the very evolution of the concept of welfare state, the very idea has been adopted in most of the democratic countries across the world. Due to which the very scope of social welfare services has expanded and become much broader. In case of Tamilnadu when the D.M.K. Party established its own Government, it was capable of realizing its prime objectives of social equality and to establish an egalitarian society. Towards realizing this ambitious target, however it has confronted several short comings and constrains to bring about the desirable changes in the living condition of the poor, downtrodden and womens of Tamilnadu. Since the DMK party from its inception, have drawn mostly, its support from the different category of backward communities womens which includes scheduled castes and scheduled tribeswomens mostly in the rural pockets it was so much concerned about their welfare, progress and development. It is needless to say that the DMK Government has accorded top priority for those the downtrodden and poverty ridden masses in the slums across the state of Tamilnadu.